Anhedonia relates to reduced striatal reward anticipation in depression but not in schizophrenia or bipolar disorder: a transdiagnostic study - Daniels, Anna; Wellan, Sarah A.; Beck, Anne; Erk, Susanne; Wackerhagen, Carolin; Romanczuk-Seiferth, Nina; Schwarz, Kristina; Schweiger, Janina; Meyer-Lindenberg, Andreas; Heinz, Andreas; Walter, Henrik (Cognitive, affective, & behavioral neuroscience, 2025)
Anhedonia, i.e., the loss of pleasure or lack of reactivity to reward, is a core symptom of major psychiatric conditions. Altered reward processing in the striatum has been observed across mood and psychotic disorders, but whether anhedonia transdiagnostically contributes to these deficits remains unclear. We investigated associations between self-reported anhedonia and neural activation during reward anticipation and consumption across patients with schizophrenia (SZ), bipolar disorder (BD), major depressive disorder (MD), and healthy controls (HC). Using the Monetary Incentive Delay paradigm, we acquired functional magnetic resonance imaging data sets in 227 participants (18-65 years), including patients with SZ (n = 44), BD (n = 47), MD (n = 56), and HC (n = 80). To capture anhedonia, three items of the Symptom Checklist-90-R were entered into exploratory factor analysis, which resulted in a single anhedonia factor. Associations between anhedonia and neural activation were assessed within a striatal region-of-interest and exploratorily across the whole brain (pFWE < .05). Self-reported anhedonia was high in MD, low in HC, and intermediate in SZ and BD. During reward anticipation, anhedonia correlated with reduced striatal activation; however, the correlation depended on diagnostic group. Specifically, the effect was driven by a negative relationship between anhedonia and dorsal striatal (putamen) activity within the MD group; for reward consumption, no correlations were found. Our results indicate that anticipatory anhedonia in MD may relate to reduced behavioral motivation via disrupted encoding of motor plans in the dorsal striatum. Future transdiagnostic research should stratify participants by anhedonia levels to achieve more homogeneous samples in terms of underlying neurobiology.
Online veröffentlicht: 30. Januar 2025
Gesehen am 05.06.2025